Are Metabolites From the Gut Microbiota Capable of Regulating Epigenetic Mechanisms in the Human Parasite Entamoeba histolytica? - Sarid, Lotem; Ankri, Serge (Frontiers in Cell and Developmental Biology, 2022)
The unicellular parasite Entamoeba histolytica inhabits the human gut. It has to adapt to a complex environment that consists of the host microbiota, nutritional stress, oxidative stress, and nitrosative stress. Adaptation to this complex environment is vital for the survival of this parasite. Studies have shown that the host microbiota shapes virulence and stress adaptation in E. histolytica. Increasing evidence suggests that metabolites from the microbiota mediate communication between the parasite and microbiota. In this review, we discuss the bacterial metabolites that regulate epigenetic processes in E. histolytica and the implications that this knowledge may have for the development of new anti-amebic strategies.